Assessing the Effectiveness of Selected Biomarkers in the Acute and Cumulative Physiological Stress Response in Professional Rugby Union through Non-invasive Assessment - Lindsay, A.; Lewis, J. G.; Scarrott, C.; Gill, N.; Gieseg, S. P.; Draper, N. (International Journal of Sports Medicine, 2015)
Rugby union is a sport involving high force and frequency impacts making the likelihood of injury a significant risk. The aim of this study was to measure and report the individual and group acute and cumulative physiological stress response during 3 professional rugby games through non-invasive sampling. 24 professional rugby players volunteered for the study. Urine and saliva samples were collected pre and post 3 matches. Myoglobin, salivary immunoglobulin A, cortisol, neopterin and total neopterin (neopterin+7,8-dihydroneopterin) were analysed by high performance liquid chromatography or enzyme linked immunosorbent assay. Significant increases in cortisol, myoglobin, neopterin and total neopterin when urine volume was corrected with specific gravity were observed (p<0.05). Significant decreases in salivary immunoglobulin A concentration were observed for games 1 and 2 while secretion rate decreased after games 2 and 3. Significant decreases were seen with the percent of 7,8-dihydroneopterin being converted to neopterin following games 2 and 3. The intensity of 3 professional rugby games was sufficient to elicit significant changes in the physiological markers selected for our study. Furthermore, results suggest the selected markers not only provide a means for analysing the stress encountered during a single game of rugby but also highlight the unique pattern of response for each individual player.
Keywords: rugby; myoglobin; cortisol; salivary immunoglobulin A; neopterin; specific gravity; creatinine